Investigation of blood antioxidant enzyme levels and glutathione peroxidase, catalase, and superoxide dismutase gene polymorphism in sheep with fluorosis - Ozbey, Ulku; Deger, Yeter; Yur, Fatmagul; Çambay, Zafer; Ozbeye, Gokben (International Society for Fluoride Research, 2017)
Reactive oxygen species have been considered to play a significant part in the development of fluorosis, a critical public health issue in many parts of the world. OBJECTIVES: The aims of this study, conducted on two groups of sheep, with and without fluorosis, was (i) to determine the effect of fluorosis on antioxidant enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and on malondialdehyde (MDA); and (ii) to investigate the relationship between the SOD, CAT, and GSH-Px genotypes and the antioxidant enzyme levels. METHODS: The two groups of sheep were: (i) 24 Akkaraman sheep with fluorosis living in Dogubeyazit province of Agri and (ii) 20 Akkaraman sheep with no signs of fluorosis living in Van. The MDA level and the antioxidant enzyme activities were identified spectrophometrically. The genotype characteristics were determined by the PCR-RFLP method using DNA extracted from blood. RESULTS: Compared to the control sheep without fluorosis, we found in the fluorotic sheep: (i) an increase in plasma MDA levels and GSH-Px-1 activity (p<0.05), and (ii) a decrease in SOD and CAT activities (p<0.01). There were significant differences found in the genotype and allele frequencies in both groups (p<0.01). CONCLUSIONS: Fluoride-induced oxidative stress affected the membrane structure resulting in elevated erythrocyte MDA levels and reduced enzyme activity of the enzymes SOD and CAT. According to our data, the gene polymorphisms show a tendency towards fluorosis for our local sheep population. © 2017, ISFR.
Keywords: Catalase; Fluorosis; Glutathione peroxidase-1; Manganese superoxide dismutase; Polymorphism